COBB-DOUGLAS FUNCTIONAL MODELLING IN ECONOMETRICS (CASE STUDY: THE IMPACT OF SALES AND OPERATIONAL EXPENSES ON NET PROFITS) - Sukmawati, Sukmawati; Ghazali, Muhammad; Afifurrahman, Afifurrahman (Program Studi Matematika, Universitas Nusa Cendana, 2023)
This study aims to determine the impact of sales and operating expenses on net income by employing a Cobb-Douglas production function. The study uses a quantitative research design which is implemented in four steps, i.e., data description and ln transformation, quality data test, regression analysis, and hypothetical test. The research sample is in the form of time-series data for the period of January 2021-December 2022, consisting of sales, operating expense, and net profit variables collected from the financial reports of Dafin Cell Store in West Lombok Regency. Our statistics analysis confirms that the sales variable significantly affects the net profits as the value 0,005 of t test is smaller than the significance level 0,05. In contrast, the operational expenses do not affect the net profits as the value 0,836 of t test is larger than 0,05. Simultaneously, both sales and operating variables affect the net profits of Dafin Cell Store since the value of 0,004 of F test is larger than 0,05. Through regression analysis we obtain the mathematical model which expresses the relationship of sales (X1), operating expenses (X2) and the net profits (Y).